2019
DOI: 10.1038/s41598-019-41205-1
|View full text |Cite
|
Sign up to set email alerts
|

A Systems Vaccinology Approach Reveals the Mechanisms of Immunogenic Responses to Hantavax Vaccination in Humans

Abstract: Hantavax is an inactivated vaccine for hemorrhagic fever with renal syndrome (HFRS). The immunogenic responses have not been elucidated yet. Here we conducted a cohort study in which 20 healthy subjects were administered four doses of Hantavax during 13-months period. Pre- and post- vaccinated peripheral blood mononuclear cells (PBMCs) and sera were analysed by transcriptomic and metabolomic profilings, respectively. Based on neutralizing antibody titers, subjects were subsequently classified into three groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 55 publications
0
18
0
1
Order By: Relevance
“…Systems vaccinology studies have uncovered metabolic pathways that correlate with vaccine immunogenicity and may have critical roles in immune response mechanisms [11,110,111] (Table 2). Metabolomic studies of influenza immunization of antibiotic-treated study participants demonstrated significant cofactor-/vitamin-related metabolism changes at Day 7 postvaccination compared to baseline [110].…”
Section: Metabolic Signatures Of Vaccine-induced Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Systems vaccinology studies have uncovered metabolic pathways that correlate with vaccine immunogenicity and may have critical roles in immune response mechanisms [11,110,111] (Table 2). Metabolomic studies of influenza immunization of antibiotic-treated study participants demonstrated significant cofactor-/vitamin-related metabolism changes at Day 7 postvaccination compared to baseline [110].…”
Section: Metabolic Signatures Of Vaccine-induced Responsesmentioning
confidence: 99%
“…In a phase III multicenter clinical trial, the Hantavax vaccination (Hantavirus vaccine) demonstrated dose-dependent upregulation of folate biosynthesis, nicotinate, nicotinamide, and arachidonic acid metabolism, thiamine levels, and pyrimidine metabolism in the high responder vaccine group [111]. In light of the known roles of metabolic pathways in immunity, Hantavax-induced perturbation of metabolites was thought to be related to immune function, including (a) folate biosynthesis with activation of cell-mediated immunity [112], (b) arachidonic acid metabolism with immune regulation [113], (c) thiamine elevation with enrichment of T cell differentiation and phagocytosis pathways [114], and (d) pyrimidine metabolism with cell-mediated immunity, T cell activation, and ultimately defeat of the microbial infection [115].…”
Section: Metabolic Signatures Of Vaccine-induced Responsesmentioning
confidence: 99%
“…However, no vaccines have yet been approved for extensive use in Europe or the Americas. In Asia, Hantavax has been used for several years the Republic of Korea (Khan et al, 2019). The vaccine is derived from formalin-inactivated Hantaan virus (HTNV)-infected suckling mouse brain, but frequent booster doses are needed for protective immunity (Aguilar et al, 2009;Avsic-Zupanc et al, 2019;Cruz et al, 2012;Hjelle et al, 1996;Montoya-Ruiz et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Oprócz tego odnotowuje się wpływ metabolitów kwasu foliowego (aktywacja odpowiedzi immu-nologicznej komórkowej) i kwasu arachidonowego (regulacja odpowiedzi, m.in. przy pomocy komórek tucznych) [13,30,39,52,53,55].…”
Section: Profilaktyka -Szczepionkiunclassified